EFFECTS OF HOME EXERCISE PROGRAMME ON SHOULDER PAIN AND FUNCTIONAL STATUS IN MALE CONSTRUCTION WORKERS - D, Malarvizhi; D, Divya; Vpr, Sivakumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To evaluate the effect of home exercise program on shoulder pain and functional status in male construction workers. Methods: Study design was quasi-experimental study, subjects were 30 male construction workers, n=15 Group A (experimental) and n=15 Group B (control). Subjects in the experimental group were instructed in a 6 weeks home exercise program, Group B subjects were treated with only ergonomic advices. The outcome measurements were visual analog scale and shoulder pain and disability index. Results: The results of this study showed that significant reduction in pain and improvement in the functional status of construction workers in Group A than Group B. Conclusion: The study concluded that there was a significant reduction in shoulder pain and improvement in functional status by home exercise program than ergonomic advices in male construction workers.